2012
DOI: 10.1016/j.jhep.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Stress management: How the unfolded protein response impacts fatty liver disease

Abstract: Summary Induction of the unfolded protein response (UPR) is recognized as central to fatty liver disease (FLD) pathophysiology. This pathway may be a potential therapeutic target for FLD, as well as other diseases. However, fundamental questions as to how UPR contributes to FLD remain unanswered. Conflicting data suggest that this pathway can both protect against and augment this disease. Here, we review the relationship between protein secretion, endoplasmic reticulum function (ER), and UPR activation. The UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…S2B). We speculate that the biphasic nature of target gene activation and xbp1 splicing reflects the transition from an adaptive UPR (at 2–12 hours) to a stressed UPR (24 hours and beyond) (Imrie and Sadler, 2012). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S2B). We speculate that the biphasic nature of target gene activation and xbp1 splicing reflects the transition from an adaptive UPR (at 2–12 hours) to a stressed UPR (24 hours and beyond) (Imrie and Sadler, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…For instance, we and others have demonstrated that ER stress induced by blocking protein glycosylation with tunicamycin is sufficient to cause steatosis (Cinaroglu et al, 2011; Henkel et al, 2009; Imrie and Sadler, 2012; Malhi and Kaufman, 2011; Puri et al, 2008; Rinella et al, 2011). However, whether the same constellation of UPR targets and effectors that become activated in this robust ER stress are also active in response to ethanol is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…82 Atf6 overexpression was sufficient to cause fatty liver in zebrafish under stress-free conditions. 82 This finding is significant because UPR induction and ER stress are possible mechanisms of FLD of many etiologies 83 and have been proposed as therapeutic targets, but until this study, the direct cause of FLD by a UPR player had not been clearly shown. Further studies are required before these findings can be tested in patients, because atf6 disruption only reduced steatosis caused by prolonged stress; in contrast, Atf6 loss increased steatosis in acute stress models of FLD.…”
Section: Metabolic and Fatty Liver Diseasementioning
confidence: 87%